Conclusions - Moloney, Colm; Lawson, John (Scottish Archaeological Internet Reports, 2006)
The results of the excavation appear to indicate that the areas investigated were located at the periphery of more intense foci of activity. It is recognised that, with hindsight, and in a modern development context, a more robust sampling strategy would have been pursued initially and that the entire development site would have been subjected to a more exhaustive programme of works including the stripping and excavation of much larger areas.